Pengembangan Lembar Kerja Peserta Didik Berbasis Metode Discovery Learning pada Materi Menulis Naskah Cerpen - Satriani Zega; Iman Pricalia Laoli; Iman Purnama Sari Laoli; Arozatulo Bawamenewi (Departement of Mathematics Education, 2023)
The goal of this project is to create a discovery learning-based junior high school curriculum for Indonesian LKPD class VIII students that covers the subject matter